2017
DOI: 10.1136/thoraxjnl-2017-210035
|View full text |Cite
|
Sign up to set email alerts
|

Change in FVC and survival in chronic fibrotic hypersensitivity pneumonitis

Abstract: The predictive value of the decline in FVC by ≥10% on survival in patients with fibrotic hypersensitivity pneumonitis is unknown. Of 112 patients included, 66 (59%) had surgical lung biopsies. Patients with ≥10% decline in predicted FVC after 6-12 months had a significantly increased risk of all-cause mortality (median survival 53 months, 95% CI 37 to 69 vs 139 months, 95% CI 66 to 212 months, p=0.007). On multivariate analysis remained associated with increasing mortality: decline in FVC by ≥10% (HR 4.13, 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 10 publications
9
106
0
3
Order By: Relevance
“…Most of the physicians surveyed performed pulmonary function tests every 3-6 months, and HRCT scans every 6-12 months, in their patients with ILDs. A decline in FVC or an increase in fibrotic changes on HRCT in patients with ILDs reflects disease progression and is predictive of mortality [24][25][26][27][28][29] . Thus regular monitoring is important for the early detection of patients with a progressive phenotype and could inform management decisions and patient counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the physicians surveyed performed pulmonary function tests every 3-6 months, and HRCT scans every 6-12 months, in their patients with ILDs. A decline in FVC or an increase in fibrotic changes on HRCT in patients with ILDs reflects disease progression and is predictive of mortality [24][25][26][27][28][29] . Thus regular monitoring is important for the early detection of patients with a progressive phenotype and could inform management decisions and patient counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Lung function tests and blood gas analyses usually have limited diagnostic value, because restrictive lung capacity and abnormal gas exchange are common to all ILDs with fibrosis [21]. However, they can help determine the severity of disease and the prognosis, and occasionally refine a working diagnosis based on disease behaviour [22][23][24][25][26][27][28]. Through serial measurements, lung function tests ( particularly FVC) provide the primary means of monitoring disease progression [21].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Studies in patients with progressive fibrosing ILDs have identified several factors that predict mortality, but these need to be interpreted carefully given the variation in the methodology used and the retrospective nature of most of the studies. Lower FVC is an established predictor of mortality in patients with progressive fibrosing ILDs, as evidenced by numerous studies spanning IPF [55][56][57], RA-ILD [4,49], SSc-ILD [58][59][60], chronic HP [61,62] and fibrotic iNSIP [53]. The same is true of DLco [55,56,60,[63][64][65], although this is harder to assess in multi-center studies due to a lack of standardization in its measurement.…”
Section: Predictors Of Disease Progression In Patients With Fibrosingmentioning
confidence: 99%
“…The same is true of DLco [55,56,60,[63][64][65], although this is harder to assess in multi-center studies due to a lack of standardization in its measurement. A decline in FVC > 10% predicted is another well-established predictor of mortality [49,56,62,65], but smaller declines in FVC have also been shown to be associated with a worse prognosis, at least in patients with IPF [66][67][68]. Further, it is important to bear in mind that "small" annual declines in FVC may become substantial when summed over a period of years.…”
Section: Predictors Of Disease Progression In Patients With Fibrosingmentioning
confidence: 99%